Prevention of Restenosis after Percutaneous Coronary Interventions: The Medical Approach - Rosanio, Salvatore; Tocchi, Monica; Patterson, Cam; Runge, Marschall S. (Thrombosis and Haemostasis, 1999)
Restenosis following successful percutaneous coronary revascularization continues to represent a major problem limiting the clinical efficacy of this procedure. The underlying mechanisms of restenosis are comprised of a combination of effects from vessel recoil, negative vascular remodeling, thrombus formation and neointimal hyperplasia. Indeed, there are important interactions among all of these mechanisms. For example, neointimal hyperplasia is stimulated by growth factors, which are released by local thrombi and the injured arterial segment itself, and act to enhance the expression of other growth-regulating proteins, in particular “second messengers“, proto-oncogenes and other cell cycle controlling proteins. This results in an inflammatory and myofibroproliferative response, which may worsen vessel narrowing caused by recoil and result in the formation of a clinically significant restenotic lesion.A multitude of pharmacologic trials have been conducted in an attempt to prevent restenosis, but most have demonstrated little benefit. Studies in smaller numbers of patients have suggested a potential benefit for several classes of agents, including: 1) the antiproliferatives, angiopeptin, trapidil and tranilast; 2) selective elimination or alteration of proliferating cells; 3) enhancement of natural growth inhibitors; and 4) signal transduction blockade or inhibition of the gene expression for various growth-stimulating proteins. Finally, there have been advances in related areas, including development of antithrombotic catheters, novel polymers, and more efficient methods for transferring genes into the vessel wall. All of these offer the possibility of delivering agents (drugs, genes, or antisense oligonucleotides) locally at the site of intervention in a way that may optimize antiproliferative effects while minimizing systemic effects – ultimately leading to a more specific inhibition of the restenosis process.
Keywords: Angioplasty; coronary artery disease; restenosis; thrombosis